2012
DOI: 10.1016/j.jad.2012.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Novel surveillance of psychological distress during the great recession

Abstract: Background Economic stressors have been retrospectively associated with net population increases in nonspecific psychological distress (PD). However, no sentinels exist to evaluate contemporaneous associations. Aggregate Internet search query surveillance was used to monitor population changes in PD around the United States’ Great Recession. Methods Monthly PD query trends were compared with unemployment, underemployment, homes in delinquency and foreclosure, median home value or sale prices, and S&P 500 tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 68 publications
(77 reference statements)
0
46
0
Order By: Relevance
“…12,17,18,25,[37][38][39]46,49,51,56,57,59, In the current recession, five studies consistently found that mental health deteriorated. 61,63,75,82,103 The most consistent results relate to suicides. Twenty-one studies examined suicides or attempted suicides and found a marked increase in these outcomes during economic downturns.…”
Section: Substance Abuse and Mental Healthmentioning
confidence: 92%
“…12,17,18,25,[37][38][39]46,49,51,56,57,59, In the current recession, five studies consistently found that mental health deteriorated. 61,63,75,82,103 The most consistent results relate to suicides. Twenty-one studies examined suicides or attempted suicides and found a marked increase in these outcomes during economic downturns.…”
Section: Substance Abuse and Mental Healthmentioning
confidence: 92%
“…Ayers et al (2012) revealed that the Standard & Poor's 500 (S & P 500) index trends were not associated with psychological distress queries (Ayers et al, 2012). Lin et al (2015) revealed that a fall in the TAIEX is associated with increases hospitalization for mental disorders, which is significant for males who are aged 45-64 years (Lin et al, 2015).…”
Section: Associations Between Different Economic Indicators and Postpmentioning
confidence: 99%
“…Women who suffer from mental stress may not consult a psychologist at the beginning. Ayers et al (2012) found that there was an increase in psychological distress queries over the Internet during the great recession (Ayers et al, 2012). In modern society, in which Internet use is popular, patients with PPD may ask for help using the Internet first instead of seeking a doctor's help.…”
Section: Limitationsmentioning
confidence: 99%
“…2,24 In fact, such financial stress has been shown to be a cause of anxiety that contributes to poor mood dysregulation, substance use, and other negative health behaviors, all of which negatively impacts cognitive reserve. 18,25,26 Another way in which employment income can facilitate cognitive reserve is through stimulating active engagement with one's environment. Income can be used for fun things in life (e.g., exotic vacations).…”
Section: Incomementioning
confidence: 99%